The Affect of Firm Size, Debt Policy, Profitability on Stock Returns: Moderating Role Dividend Policy - Subing, Hesty Juni Tambuati; Apriansyah, Poni Melati (Research of Finance and Banking, 2024)
This research aims to examine the influence of Firm Size, Debt Policy and Profitability on Stock Returns with Dividend Policy as a moderating variable in non-financial Firms included in the LQ45 stock index on the Indonesia Stock Exchange (BEI) for the 2017-2022 period. The sampling technique in this research is the purposive sampling technique. This research uses secondary data, namely the firm's annual financial report (annual report) obtained from the official website of the Indonesian Stock Exchange (IDX). The analytical method used is multiple linear regression techniques and moderated regression analysis (MRA) with testing using the SPSS version 29.0 application. The research results show that Firm size has a positive and significant effect on stock returns. Debt policy and profitability have a negative and insignificant effect on stock returns. Dividend policy can moderate Firm size on stock returns. However, dividend policy does not moderate debt policy and profitability on stock returns; however, dividend policy can moderate the influence of Firm size, debt policy, and profitability simultaneously on stock returns. The managerial implications of this research show that Firm size, debt policy, and profitability have a significant influence on stock returns, while dividend policy can moderate this relationship.